2000
DOI: 10.1086/315824
|View full text |Cite
|
Sign up to set email alerts
|

Sulfa or Sulfone Prophylaxis and Geographic Region Predict Mutations in thePneumocystis cariniiDihydropteroate Synthase Gene

Abstract: To determine factors associated with mutations in the Pneumocystis carinii dihydropteroate synthase (DHPS) gene, a prospective study of human immunodeficiency virus (HIV)-infected patients with confirmed P. carinii pneumonia was conducted in Atlanta, Seattle, and San Francisco. Clinical information was obtained from patient interview and chart abstraction. DHPS genotype was determined from DNA sequencing. Overall, 76 (68.5%) of 111 patients had a mutant DHPS genotype, including 22 (81.5%) of 27 patients from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 30 publications
7
124
4
Order By: Relevance
“…Recent studies investigating mutations in the gene encoding dihydropteroate synthase have shown a correlation not only with prior sulfur prophylaxis or treatment but also with geographical location, indicating transmission either directly or through a common environmental source (3,12). In addition, in a study examining P. carinii transmission, P. carinii DNA was found in nasopharyngeal samples from the mother, doctor, and nurse caring for an HIV-negative child with P. carinii pneumonia but not in 30 control hospital staff members who did not have contact with the infected patient (37).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies investigating mutations in the gene encoding dihydropteroate synthase have shown a correlation not only with prior sulfur prophylaxis or treatment but also with geographical location, indicating transmission either directly or through a common environmental source (3,12). In addition, in a study examining P. carinii transmission, P. carinii DNA was found in nasopharyngeal samples from the mother, doctor, and nurse caring for an HIV-negative child with P. carinii pneumonia but not in 30 control hospital staff members who did not have contact with the infected patient (37).…”
Section: Discussionmentioning
confidence: 99%
“…Prior exposure to sulfonamide drugs has been identified as a predictor of mutant genotypes (reviewed in Totet et al, 2004). In addition the city in which a patient resides has also been identified as an independent risk factor (Huang et al, 2000;Kazanjian et al, 2000), a factor that supports the hypothesis that P. jirovecii is transmitted from infected treated patients to susceptible untreated patients, either directly or through a common envi-ronmental source. Totet and colleagues identified P. jirovecii genotypes at the DHPS locus in immunocomptetent infants with primary infection and immunosuppressed adults with PCP (Totet et al, 2004).…”
Section: Transmission Of Possible Resistant P Jirovecii Organisms Inmentioning
confidence: 99%
“…As PCR assay is infrequently applied as a diagnostic method for PCP on respiratory samples, colonised patients with P. carinii may be missed [8]. Huang et al [9] have recently reported that a high proportion of mutant genotypes of P. carinii among HIV-infected individuals in a localised region provides the evidence of person-to-person transmission of the organism either directly or through a common environmental source. Transmission of P. carinii DNA from a patient with PCP to immunocompetent contact health-care workers has also been described [10].…”
Section: Introductionmentioning
confidence: 99%